Association between neutrophil percentage-to-albumin ratio and rheumatoid arthritis: a cross-sectional study from US population, 1999–2018 - Liu, Di; Zhang, Jing; He, Lan; An, Qi; Xu, Qianyun; Zhang, Shusen; Cao, Ruoyan (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is linked to systemic inflammation and immune dysregulation. The neutrophil-percentage-to-albumin ratio (NPAR), integrating neutrophil activity and nutritional status, may reflect inflammatory and immune responses. However, its association with RA remains unexplored. We aimed to investigate the relationship between NPAR and RA using data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018.MethodsThis cross-sectional study utilized data from NHANES including 38,272 participants. The NPAR was calculated based on the neutrophil percentage (in total WBC count) (%), and albumin value (g/dL). We employed weighted multivariable logistic regression analysis and subgroup analysis to examine the association between NPAR and RA, adjusting for sociodemographic, lifestyle, and clinical covariates. Restricted cubic splines were used to assess potential non-linear relationships. Additionally, receiver operating characteristic (ROC) was performed to determine the predictive accuracy of NPAR compared with other inflammatory markers.ResultsAfter adjusting for all covariates, multivariable logistic regression indicated that elevated levels of NPAR were significantly associated with an increased risk of RA (ORtertile3vs1 = 1.27, 95% CI: 1.11-1.44). A nonlinear, reverse L-shaped relationship was observed, with RA risk rising significantly when NPAR exceeded 13.6 (Pnon-linearity = 0.004). Subgroup analyses confirmed consistency across populations. NPAR demonstrates a superior predictive capability for RA risk when compared to other established markers, including Systemic Immune-Inflammation Index (SII), Systemic Inflammation Response Index (SIRI), Platelet-to-Lymphocyte Ratio (PLR), Monocyte-to-Lymphocyte Ratio (MLR), and Neutrophil-to-Lymphocyte Ratio (NLR).ConclusionOverall, our study demonstrates a significant positive association between NPAR and RA prevalence in U.S. adults, particularly when NPAR levels exceeded 13.6. Our findings underscore the critical role of immune-nutritional interactions in RA pathogenesis. However, owing to the cross-sectional design, prospective longitudinal investigations are warranted to establish causality and elucidate underlying biological mechanisms.